Sains dan Sastra Pada Zaman Dinasti Abbasiyah - Cecep Hidayat; Taufik Hidayat; Sandi Yoga Permana (Program Studi Sejarah Peradaban Islamm UIN Raden Fatah Palembang, 2024)
The Abbasid Dynasty (750-1258 CE) stands as one of the most illustrious periods in Islamic history, marked by significant advancements in science and literature. These achievements were driven by several factors, including political stability, economic prosperity, and government policies that promoted research and education. During this era, Baghdad, the capital of the caliphate, emerged as the intellectual hub of the world, attracting scholars, philosophers, and writers from diverse backgrounds.Science during the Abbasid Dynasty encompassed various disciplines such as mathematics, astronomy, medicine, chemistry, and physics. Muslim scholars not only translated classical works from Greek, Persian, and Indian sources into Arabic but also conducted original research and made substantial innovations. Figures like Al-Khwarizmi, known as the father of algebra, and Al-Razi, a pioneer in medicine, symbolize the scientific achievements of this period.In the realm of literature, the Abbasid era also witnessed remarkable growth. Poetry, prose, and other literary works flourished, with contributions from notable writers such as Al-Jahiz and Al-Mutanabbi. These literary works not only reflect the cultural and intellectual richness of the time but also provide insights into the social and political life under the Abbasid caliphate.Several factors contributed to these advancements, including the presence of large libraries such as the House of Wisdom (Bayt al-Hikma), which served as centers for translation and research, and the patronage of caliphs who supported the development of science and the arts. The synergy between political stability, economic support, and visionary government policies created an environment conducive to the progress of science and literature.Thus, the Abbasid Dynasty not only represents a significant milestone in Islamic history but also greatly contributed to the advancement of human civilization through its achievements in science and literature.